2016
DOI: 10.1111/cob.12134
|View full text |Cite
|
Sign up to set email alerts
|

Dietary restraint: what's the harm? A review of the relationship between dietary restraint, weight trajectory and the development of eating pathology

Abstract: Dietary restraint has historically been implicated as a risk factor for the development of eating pathology. Despite existing findings, recent research suggests that many individuals are capable of practicing dietary restraint without negative effects. In order to successfully incorporate the positive aspects of dietary restraint into interventions for healthy weight management, a nuanced examination of the relationship between dietary restraint and resulting eating patterns is necessary. Accordingly, the curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
153
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(169 citation statements)
references
References 113 publications
(158 reference statements)
10
153
0
6
Order By: Relevance
“…However, these are often encouraged or are a necessary component of obesity treatment. It is important to note that dietary restraint, often used as a measure of dieting practice in prospective cohort studies, may not reflect actual energy restriction . Consequently, the energy restriction itself may not increase eating pathology .…”
Section: Discussionmentioning
confidence: 99%
“…However, these are often encouraged or are a necessary component of obesity treatment. It is important to note that dietary restraint, often used as a measure of dieting practice in prospective cohort studies, may not reflect actual energy restriction . Consequently, the energy restriction itself may not increase eating pathology .…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, some researchers have shown that dietary restraint may lead to binge eating, whereas other studies have found insignificant effects when investigating the relationship between dietary restraint and binge eating (De Young et al, 2014; Elran-Barak et al, 2015; Goldschmidt, Wall, Loth, Le Grange, & Neumark-Sztainer, 2012; Mackinnon et al, 2011; Schaumberg, Anderson, Anderson, Reilly, & Gorrell, 2016). Although these conflicting findings may be due to methodological differences, they might also be contributed to the possibility of a third variable (Stice, 2002).…”
Section: Dietary Restraint and Binge Eatingmentioning
confidence: 99%
“…It is important to note that measures of dietary restraint fail to predict an actual lower caloric intake and thus are not valid measures of caloric restriction [23]. Instead, dietary restraint refers to the cognitive effort to restrict food, regardless of the behavioral outcome of this effort [24]. The items of the dietary restraint scale of the EPI-C [22] were more closely aligned with the rigid control dimension of dietary restraint (i.e., all-or-nothing approach to dieting) rather than the flexible control dimension (i.e., a more graduated approach to dieting, in which “fattening” foods are eaten in limited quantities without the feeling of guilt) [25].…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Schacht et al [22], dietary restraint was the only dimension that was associated with a higher BMI. Alternatively, increases in dietary restraint may represent an attempt to control weight in response to weight gain [24]. Of note, there is no study available that has compared the EPI-C dietary restraint scale with other measures of dietary restraint.…”
Section: Discussionmentioning
confidence: 99%